Public good issues in TARGET: natural monopoly, scale economies, network effects and cost allocation - Wilko Bolt; David Humphrey (European Central Bank (ECB), 2005)
This paper discusses various theoretic concepts which play a role in assessing the public benefits of Target, the large value RTGS payment network operated by the Eurosystem. These concepts touch upon natural monopoly, network externalities, competition and contestability, as well as economies of scale and scope. The existence of a natural monopoly provides a rationale for a temporary partial or full subsidy in order for Target to achieve the `most efficient scale' or apply the most efficient technology to lower unit costs. Such a subsidy could be implemented through temporary 'penetration' pricing. Based on empirical results for the Federal Reserve's payment system (Fedwire), it is further argued that if Target decided to standardize its operating platforms and consolidate its processing sites into one or a few centers, it too could realize strong scale economy benefits and lower unit costs.
Keywords: G20; H41; L10; 330; most efficient scale; natural monopoly; partial subsidy; public good; Zahlungsverkehr; Öffentliche Güter; Natürliches Monopol; Skalenertrag; Netzwerkökonomik